Katulong, drayber, at Metro Aide - Aguilar, Mila D.; Alfonso, Gigi Javier; Selvido, Ma. Ernie Selvido (Pinoy Tok, 1989)
Reveals the joys and sacrifices of being a housemaid, the challenges of a jeepney or taxi driver, and the importance of street sweepers known as Metro Aides.